Relationship between Age and the Ability to Break Scored Tablets - Notenboom, Kim; Vromans, Herman; Schipper, Maarten; Leufkens, Hubert G. M.; Bouvy, Marcel L. (Frontiers in Pharmacology, 2016)
Background: Practical problems with the use of medicines, such as difficulties with breaking tablets, are an often overlooked cause for non-adherence. Tablets frequently break in uneven parts and loss of product can occur due to crumbling and powdering. Health characteristics such as the presence of peripheral neuropathy, decreased grip strength and manual dexterity, can affect a patient’s ability to break tablets. As these impairments are associated with ageing and age-related diseases such as Parkinson's disease and arthritis, difficulties with breaking tablets could be more prevalent among older adults. The objective of this study was to investigate the relationship between age and the ability to break scored tablets. Methods: A comparative study design was chosen. Thirty-six older adults and thirty-six young adults were systematically observed with breaking scored tablets. Twelve different tablets were included. All participants were asked to break each tablet by three techniques: in between the fingers with the use of nails, in between the fingers without the use of nails and pushing the tablet downward with one finger on a solid surface. It was established whether a tablet was broken or not, and if broken, whether the tablet was broken accurately or not. Results: The older adults experienced more difficulties to break tablets compared to the young adults. On average, the older persons broke 38.1% of the tablets, of which 71.0% was broken accurately. The young adults broke 78.2% of the tablets, of which 77.4% was broken accurately. Further analysis by mixed effects logistic regression revealed that age was associated with the ability to break tablets, but not with the accuracy of breaking. Conclusions: Breaking scored tablets by hand is less successful in an elderly population compared to a group of young adults. Health care providers should be aware that tablet breaking is not appropriate for all patients and for all drugs. In case tablet breaking is unavoidable, a patient’s ability to break tablets should be assessed by health care providers and instructions on the appropriate method of breaking should be provided.